Once bitten, twice shy: Failed deals and subsequent M&A cautiousness - Robert J. Campbell; Peter Limbach; Johannes Reusche (University of Cologne, Centre for Financial Research (CFR), 2022)
Companies occasionally are unable to finalize publicly announced M&A bids-a phenomenon we refer to as failed deals. Despite their commonality, the implications of failed deals for bidding firms are not well understood. We thus theorize about and empirically investigate the relationship between failed deals and subsequent M&A behavior. In doing so, we present multiple reasons for what we term "the once bitten, twice shy effect," whereby firms act more cautiously in the M&A context following failed deals. In a sample of M&As across North American and European firms, we find empirical support consistent with our theorizing suggesting the cautiousness following failed deals results in a longer time-period between M&A bids, smaller target firm size, and a greater likelihood of advisor usage.
Keywords: 330; mergers and acquisitions; corporate strategy; failed deals; risk and decision making; M&A activity